Ensuring the Integrity of Digital Evidence: The Role of the Chain of Custody in Digital Forensics - Premanand Narasimhan,; Dr.N.Kala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Chain of Custody (CoC) is a critical procedural safeguard in digital forensics, ensuring the reliability, credibility, and admissibility of digital evidence in legal proceedings. This paper explores the significance, stages, and challenges associated with maintaining a robust CoC. Through case studies and best practices, the paper underscores how adherence to CoC principles sustains the integrity of forensic investigations. References from books, journals, blogs, YouTube, Open Educational Resources (OERs), government and private reports enrich the discussion.